Answer:
x = -20/9
Step-by-step explanation:
First we need to distribute this equation 4(4x+1) = 3x-4(6-x)+8. After distributing we get 16x+4 = 3x-24+4x+8. Next we add like terms to get 16x+4 = 7x-16. Now subtract 7x on both sides to get 9x+4 = -16. Now subtract -4 on both sides to get 9x = -20. Now divide by 9 on both sides to get x= -20/9.
Hope that helps! :)
Answer:
x = t
y = -t
z = (17-6t)/5
Step-by-step explanation:
First we will write down Equation 1 and Equation 2
4x-2y+5z = 17------(1)
x + y = 0--------(2)
Since we are asked to express our answer in terms of the parameter t so lets suppose x = t and y = -t
Now substitute the value of x and y in equation (1) we get
4(t) -2(-t) +5z = 17
6t + 5z = 17
5z = 17 -6t
z = (17-6t)/5
hence we get the following answer
x = t
y = -t
z= (17-6t)/5
we can also verify our answer by substituting the values of x ,y and z in any of the two equations above, for example lets substitute these values in equation 1
4(t) -2(-t) + 5((17-6t)/5)) = 17
6t + 17 -6t = 17
6t -6t = 17 -17
0 = 0
16.) 38.25= 4.25h
divide by 4.25 on both sides
h=9
17.)214= 1/3x
divide by 1/3 on both sides
x= 642
18.)70= 2x
divide by 2 on both sides
x=35
19.)18.69= 5.25+1.68x
subtract 5.25 on both sides
13.44=1.68x
divide by 1.68 on both sides
x=8
Answer:
i honestly have no clue
Step-by-step explanation: yeah
Answer:
-24
Step-by-step explanation:
Given expression:
3z (2y - 4)²
z = -2 and y = 3
To solve this problem, simply substitute:
3z (2y - 4)² = 3(-2){2(3) - 4}²
= -6(6-4)²
= -6 (2)²
= -6 x 4
= -24